Application of rhetoric in the Malay-language scholarly books as a product marketing strategy - Mohd Asri, Nurul Fadzlin; Sha’ri, Sharil Nizam; Kamaruddin, Rohaidah; Hamzah, Zaitul Azma Zainon; Che Rodi, Rozita (Human Resource Management Academic Research Society, 2021)
Rhetoric in the writing of scholarly books published by publishers in public universities and government institutions or the Majlis Penerbitan Ilmiah Malaysia (MAPIM) is a marketing strategy used upon the society, but is not known to the public. In fact, little academic research has been conducted on the book publishing industry in the country, even though this scholarly genre is proven to record specific expertise and fields to be shared, and at the same time needed by the community. Thus, this study aims to identify the type of rhetoric used in selected Malay-language scholarly books in connection with the marketing strategy practiced by MAPIM Publishers and analyze the use of rhetoric in selected Malay-language scholarly books by applying the Modern Rhetorical Theory (1993) by Enos and Brown. This study uses text analysis methods to analyze rhetoric in scholarly books. This study found three modes of rhetoric, which are, descriptive rhetoric, explosive rhetoric, and argumentative rhetoric have been well-used in the writing of Malay-language scholarly books as a strategy to disseminate knowledge through captivating language and also guarantee effective delivery of information. This is in line with the main objective of MAPIM to ensure that high-quality scholarly books can be offered as a product that meets the needs of the target group as the development of scholarship to the community.